Dropout from interpersonal psychotherapy for mental health disorders: A systematic review and meta-analysis. (8th October 2019) - Linardon, Jake; Fitzsimmons-Craft, Ellen E.; Brennan, Leah; Barillaro, Mary; Wilfley, Denise E.
Abstract: Objective: Dropout is one factor that might limit the effectiveness of interpersonal psychotherapy (IPT). Improved understanding of IPT dropout is an important research priority. This meta-analysis examined dropout rates from IPT in randomized controlled trials. Method: Seventy-two trials met inclusion criteria. Results: The weighted mean dropout rate from IPT was 20.6% (95% CI = 17.4–24.2). Dropout rates were similar for depressive (20.9%; 95% CI = 17.2–25.2), anxiety (16.1%; 95% CI = 11.1–22.9), and eating disorders (18.7%; 95% CI = 11.6–28.8). Dropout was highest when more stringent definitions of dropout were applied (e.g., failure to complete the entire IPT protocol versus failure to complete at least 50% of sessions) and was lowest when adolescent patients were sampled. There was some evidence that IPT was associated with significantly lower rates of dropout than both CBT and non-specific supportive therapies. These effects were generally replicated when analysing trials that provided a clear definition of treatment (rather than study) dropout. Conclusions: Overall, findings provide preliminary evidence to suggest that IPT may be an accepted and tolerated treatment option for patients with common mental health disorders. This review also highlights the need for future trials to rigorously report detail pertaining to patient dropout.